a) 3x.( 5x ² – 2x – 1 ) b) ( x ² + 2xy – 3 ) . ( -xy )

Question

a) 3x.( 5x ² – 2x – 1 )
b) ( x ² + 2xy – 3 ) . ( -xy )

in progress 0
Piper 8 phút 2021-09-09T14:14:28+00:00 2 Answers 0 views 0

Answers ( )

    0
    2021-09-09T14:15:33+00:00

    a) 3x . ( 5x² – 2x – 1 )

    = 3x . 5x² – 3x . 2x – 3x . ( -1)

    = 15x³ – 6x² – 3x 

    b) ( x² + 2xy – 3 ) . ( -xy )

    = ( -xy ) . ( x² + 2xy – 3 )

    = ( -xy ) . x² + ( -xy ) . 2xy – ( -xy ) . ( -3 )

    = ( -x³y )- 2x²y²+3xy

    0
    2021-09-09T14:15:58+00:00

    a,3x(5$x^{2}$ -2x+1)

    =15$x^{3}$-6 $x^{2}$-3x

    b,($x^{2}$+2xy-3)(-xy)

    =-$x^{3}$y-2 $x^{2}$$y^{2}$+3xy

Leave an answer

Browse

35:5x4+1-9:3 = ? ( )